MAKNA PERSATUAN DAN KEPEDULIAN DALAM PERTUMBUHAN GEREJA MULA-MULA BERDASARKAN KISAH PARA RASUL 2:1-47 - Suryady, Robertus (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
This research examines the meaning of unity and care in the growth of the early church based on Acts 2:1-47. Unity and care are two fundamental values that become the main foundation in building a healthy, harmonious, and dynamic faith community. This study uses a qualitative-theological approach with literature study as the main method, combining analysis of biblical texts and review of theological literature and previous research on early church growth. The main arguments of this study include: (1) unity as the foundation of church growth that strengthens spiritual and social bonds, (2) care as a form of love that strengthens solidarity and service in the community, and (3) synergy between unity and care that encourages holistic church growth. The study results show that unity and care not only complement each other but also become an effective driving force in building a vibrant and fruitful church. The theological and practical implications of this study emphasize the importance of strengthening the fellowship of prayer, teaching the word, and sincere social service in the context of today's church. This research provides strategic recommendations for the development of the contemporary church in order to emulate the Christian values that have proven to be the key to the growth of the early church.